Baroque fictions : revisioning the classical in Marguerite Yourcenar - Colvin, Margaret Elizabeth (Amsterdam ; New York : Rodopi, 2005)
This volume is the first in-depth study of the French novelist Marguerite Yourcenar's fiction to contend that the author's texts exhibit in unexpected ways numerous characteristics of the neobaroque. This subversive, postmodern aesthetic privileges extravagant artistic play, flux, and heterogeneity. In demonstrating the affinity of Yourcenar's texts with the neobaroque, the author of this study casts doubt on their presumed transparency and stability, qualities associated with the French neoclassical tradition of the past century, where the Yourcenarian œuvre is most often placed. Yourcenar's.
A frontispiece -- Marguerite Yourcenar and the writing of fiction: an aesthetic imperative -- Anna, Soror ... : Neobaroque sacralizes the abject -- Denier du rêve: Baroque discourses, fascist practices -- Neobaroque humanism: "Sounding the Abyss" in L'Œuvre au Noir -- Neobaroque confessions: un homme obscur and the oppressive superficiality of words -- An author for the new millennium -- Selected works cited and consulted -- Index of proper names.
Originally presented as the author's thesis (doctoral)--University of Connecticut, 2004.
Includes bibliographical references (pages 165-173) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Keywords: Yourcenar, Marguerite; Yourcenar, Marguerite -- Critique et interprétation.; Yourcenar, Marguerite; Classicism in literature; Baroque literature -- History and criticism; Classicisme dans la littérature.; Littérature baroque -- Histoire et critique; LITERARY CRITICISM -- European -- French; Criticism, interpretation, etc